Achieving inclusive growth? Wage dynamics in Cambodia, Laos and Vietnam. Issue 1 (31st December 2022) - Morlok, Michael; Teutoburg-Weiss, Hannes; Khounvilay, Keonakhone; Huu Luyen, Nguyen; Ven, Seyhah
ABSTRACT: This paper assesses whether industrial growth in Cambodia, Laos and Vietnam has been inclusive. While inclusiveness of growth is both a highly debated topic in the development discourse and an official government ambition in all three countries, it has not been assessed systematically in this context. In this paper, we focus specifically on one aspect of inclusiveness by examining the wage inequality between five occupational levels in the manufacturing sector. Based on survey data of companies operating in the electronics, food and beverage, and garment sectors, we show that average wage levels have increased for all occupational levels (although at different rates). We observe a U-shaped wage growth distribution, and argue that this could be a result of automation, dependency on foreign buyers, or an oversupply of pre-employment training programs at the technician level. We further observe particularly high wage growth for lower occupational levels in Cambodia and Laos – indicating relatively inclusive wage growth. In Vietnam, however, there is a development towards more wage inequality. Lastly, our study finds a clear convergence effect in the manufacturing sector; here, improved market information or increased labor mobility and reallocation of (training) resources could be contributing factors.